Comparable Outcomes Between Native and Periprosthetic Fractures of the Distal Femur - Kaufman, Matthew W.; Rascoe, Alexander S.; Hii, Jeffrey L.; Thom, Mitchell L.; Levine, Ari D.; Wilber, Roger G.; Hirschfeld, Adam G.; Romeo, Nicholas M.; Wera, Glenn D. (The Journal of Knee Surgery, 2022)
Despite the rising prevalence of arthroplasty and aging population, limited data exist regarding differences in periprosthetic fracture clinical outcomes compared with native counterparts. This study compares differences in hospital treatment, morbidity, and mortality associated with periprosthetic distal femur fractures at an urban level 1 trauma center. We retrospectively reviewed all adult AO/OTA type 33 fractures (526) that presented to our institution between 2009 and 2018. In total, 54 native and 54 periprosthetic fractures were matched by age and gender. We recorded demographics, operative measures, length of stay (LOS), discharge disposition, and mortality. We used McNemar's and paired t-tests for analysis where appropriate (p < 0.05) (IBM SPSS Statistics for Windows, Version 26.0. Armonk, NY; IBM Corp.). The average age at injury was 74 years ± 12 (native) compared with 73 years ± 12 (periprosthetic). After 1:1 matching, the groups had similar body mass index (31.01 vs. 32.98, p = 0.966 for native and periprosthetic, respectively) and mechanisms of injury with 38 native and 44 periprosthetic (p = 0.198) fractures from low-energy falls. Both groups had 51/54 fractures managed with open reduction internal fixation with a locking plate. The remaining were managed via amputation or intramedullary nail fixation. Mean operative time (144 minutes (±64) vs. 132 minutes (±62), p = 0.96) and estimated blood loss (319 mL (±362) vs. 289 mL (±231), p = 0.44) were comparable between the native and periprosthetic groups, respectively. LOS: 9 days ± 7 (native) versus 7 days ± 5 (periprosthetic, p = 0.31); discharge disposition (to skilled nursing facility/rehab): n = 47 (native) versus n = 43 (periprosthetic, p = 0.61); and mortality: n = 6 (native) versus n = 8 (periprosthetic, p = 0.55). No significant differences were observed. We found no statistical differences in morbidity and mortality in periprosthetic distal femur fractures treated over 10 years at a level 1 trauma center. Native and periprosthetic AO/OTA type 33 distal femur fractures are serious injuries with similar outcomes at a level 1 trauma center.
Keywords: arthroplasty; trauma; periprosthetic fracture; outcomes